Exploring the Influence of Parental Personality Types on Children’s Academic Choices (Journal of Science, Technology and Innovation Policy, 2024)
The academic decisions that children make are frequently influenced by several different circumstances. One of the most important yet understudied aspects of this is the influence of the personality types of their parents. The objective of this report is to understand how parental personalities may impact a child's inclination towards science or art subjects. The Myers-Briggs Type Indicator (MBTI) Test was used for parents to indicate the relationship between parental personality type and the academic choices made by their children, particularly in the field of science and art. The results indicated that children from the INTJ, INFJ, and ENFJ parents’ personality types, are likely to choose science subjects, while children from ENTJ parents’ personality types choose art subjects. This sheds light on the association between parental personality types and children's academic choices; aiding educators and policymakers better tailor educational approaches to accommodate diverse student needs and aspirations.
Keywords: Personality Types, Myers-Briggs Type Indicator (MBTI), Children’s Academic Choices